Perfect Forward Secure ID-based Key Agreement Protocol in Group Communication - Pengshuai Qiao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Several identity-based key agreement protocols using bilinear pairing have been proposed in recent years and none of them has achieved all required security properties. In this paper, we firstly propose an ID-based one round authenticated group key agreement protocol with bilinear pairings, where all participants can generate the group session key in one round. Based on the intractability of elliptic curve discrete logarithm problem, every user’s private key can be proved to be secure. Also an extended version of one round authenticated group key agreement protocol is given, it provide perfect forward secrecy and avoid key escrow by the Key Generation Center.  Finally, a comprehensive security analysis and a comprehensive security analysis are provided. By comparing with other protocols, the proposed protocol requires lower computation cost.